Clinio-pathological changes in goats challenged with Corynebacterium peudotuberculosis and its exotoxin (PLD) - Jeber, Zaid Khuder Mahmood; Abdullah, Faez Firdaus Jesse; Saharee, Abdul Aziz; Sabri, Jasni; Yusoff, Rosnina; Haron, Abd Wahid (Science Publications, 2015)
Caseous lymphadenitis (CLA) is a chronic disease caused by Corynebacterium pseudotuberculosis. However, there is a paucity of data about the C. pseudotuberculosis exotoxin, phospholipase D (PLD) response during the course of CLA. Therefore, this study was conducted to observe the clinical signs and the cellular changes after an experimental infection of the C. pseudotuberculosis and phospholipase D challenge. Twenty six crossbred Boer goats aged 12-14 months were divided into 3 groups; the first group n=6 was inoculated with 1ml sterile PBS s.c. as the control. The second group n=10 was inoculated with live C. pseudotuberculosis 1×109 cfu s.c. The third group n=10 was i.v. inoculated with PLD 1mL/20 kg, BW. Both the C. pseudotuberculosis and the PLD treated groups showed a significant increase (p<0.05) in body temperature, heart rate, respiratory rate and body score. Pathologically, the C. pseudotuberculosis and the PLD treated groups showed a significant cellular changes (p<0.05) manifested as edema, congestion, infiltration of inflammatory cells mainly lymphocytes and macrophages, hemorrhage, degeneration and necrosis in the visceral organs including the lungs, heart, liver, spleen, kidneys and lymph nodes. C. pseudotuberculosis infected group showed abscessation of the lymph nodes and some of the visceral organs. In contrast, PLD inoculation did not lead to any abscess formation in the lymph nodes neither in the visceral organs. It concluded that the C. pseudotuberculosis caused typical CLA disease with short incubation period of two weeks. The PLD inoculation showed little clinical signs and it did not lead to abscesses formation externally neither internally, however, it caused obvious cellular changes in the visceral organs as well as in the lymph nodes. PLD play a key role in CLA development, yet it is impossible to trigger granulomatous lesion without the C. pseudotuberculosis being present.